Quality control guidelines for clinical-grade human induced pluripotent stem cell lines. (12th September 2018) - Sullivan, Stephen; Stacey, Glyn N; Akazawa, Chihiro; Aoyama, Naoki; Baptista, Ricardo; Bedford, Patrick; Bennaceur Griscelli, Annelise; Chandra, Amit; Elwood, Ngaire; Girard, Mathilde; Kawamata, Shin; Hanatani, Tadaaki; et al.
Use of clinical-grade human induced pluripotent stem cell (iPSC) lines as a starting material for the generation of cellular therapeutics requires demonstration of comparability of lines derived from different individuals and in different facilities. This requires agreement on the critical quality attributes of such lines and the assays that should be used. Working from established recommendations and guidance from the International Stem Cell Banking Initiative for human embryonic stem cell banking, and concentrating on those issues more relevant to iPSCs, a series of consensus workshops has made initial recommendations on the minimum dataset required to consider an iPSC line of clinical grade, which are outlined in this report. Continued evolution of this field will likely lead to revision of these guidelines on a regular basis.